Study guides

☆☆

Q: What is the value of x in 6-3x equals 5x-10x plus 12?

Write your answer...

Submit

Still have questions?

Related questions

-3x + 6 = -30 -3x = -30 - 63x = 36x = 36/3Therefore, x = 12.

It is 2x2 - 7x + 9

3x + y + z = 63x - y + 2z = 9y + z = 3y + z = 3y = 3 - z (substitute 3 - z for y into the first equation of the system)3x + y + z = 63x + (3 - z) + z = 63x + 3 = 63x = 3x = 1 (substitute 3 - z for y and 1 for x into the second equation of the system)3x - y + 2z = 93(1) - (3 - z) + 2z = 93 - 3 + z + 2z = 93z = 9z = 3 (which yields y = 0)y = 3 - z = 3 - 3 = 0So that solution of the system of the equations is x = 1, y = 0, and z = 3.

3x+2=2x+8x=63x+2 = 2x + 8; first subtract 2x from both sidesx+2=8; then subtract 2 from both sidesx=6

(14x^3 - 10x^2) = 2x^2(7x - 5) 63x - 45 = 9(7x - 5) 14x^3 - 10x^2 + 63x - 45 = (2x^2 + 9)(7x - 5)

63x/49 = 9x/7

189xy

3x + 6y = 363x - 6y = 0 add both equations6x = 36x = 63x - 6y = 03(6) - 6y = 018 - 6y = 018 = 6y3 = yThe solution point is (6, 3).

In 63x=9. X=0.142857142857143. So 63(0.142857142857143)=9 or 63(1/7) = 9

If what you mean is F(x) = 63x then the range is all real numbers.

6x + 73 < 3x + 103x + 73 < 103x < -63x < -21The largest whole number that complies is -22.

it's an easy one :)-6 - 6x = 9 - 9x-6x + 9x = 9 + 63x = 15x = 15/3X = 5

People also asked